Ventilatory oscillations at exercise in hypoxia: A mathematical model. (21st December 2016) - Hermand, Eric; Lhuissier, François J.; Voituron, Nicolas; Richalet, Jean-Paul
Abstract: We evaluated the mechanisms responsible for the instability of ventilation control system under simultaneous metabolic (exercise) and environmental (hypoxia) stresses, promoting the genesis of periodic breathing. A model following the main concepts of ventilatory control has been tested, including cardiovascular and respiratory parameters, characteristics of peripheral and central chemoreceptors, at mild exercise in hypoxia (FIO2 =0.145). Interaction between O2 and CO2 sensing was introduced following three different modalities. A sensitivity and multivariate regression analyses closely matched with physiological data for magnitude and period of oscillations. Low FIO2 and long circulatory delay from lungs to peripheral chemoreceptors (DeltaTp) lengthen the period of oscillations, while high peripheral and central chemoresponses to O2 and CO2, low FIO2 and high DeltaTp increased their magnitude. Peripheral and central O2 /CO2 interactions highlight the role of CO2 on peripheral gain to O2 and the contribution of peripheral afferences on central gain to CO2 . Our model supports the key role of peripheral chemoreceptors in the genesis of ventilatory oscillations. Differences in the dynamics of central and peripheral components might be determinant for the system stability. Highlights: We evidenced the existence of a respiratory oscillator with a 11-second period, during concomitant exercise and hypoxia. A mathematical model of human ventilation control points out significant parameters impacting its stability. Breathing stability is mainly affected by characteristics of chemoreceptors, circulation delays and O2 -CO2 interactions. A phase shift between central and peripheral signals modulates the magnitude of ventilatory oscillations. The phase shift also modifies the type of contribution of chemoreceptors: hypoadditive, additive or hyperadditive.